STRATEGI DAN INOVASI GURU PAI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI MASA PANDEMI COVID-19 - Hari Alih Hansyah; Zainal Arifin; Ajat Rukajat (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
STRATEGIES AND INNOVATIONS FOR ISLAMIC RELIGIOUS EDUCATION (PAI)  TEACHERS IN INCREASING STUDENT LEARNING MOTIVATION DURING THE COVID-19 PANDEMICThis study seeks to explore the learning process of PAI student learning during the Covid-19 pandemic and how the strategies and innovations of Islamic Education teachers in increasing students' motivation. During the COVID-19 pandemic, the government currently made a policy so that students learn online (online) using internet-based media (online) or commonly called PJJ (Distance Learning), causing students to be required to learn from home (BDR) without can PTM (Face-to-Face Learning) at school or in class directly. This condition certainly greatly affects the student's learning motivation which is decreasing, due to ineffectiveness and the lack of interactive and communication between teachers and students during PJJ. This research method uses qualitative research methods and data collection techniques by means of observation, interviews and documentation where the object of research is the PAI teacher and students of class X IPA 6 at SMAN 5 Karawang. This research shows that there has been a decrease in student motivation during the COVID-19 pandemic with an indicator that many students are not present when the teacher delivers PJJ material and assignments are not done on time, and some do not even do assignments at all. The development of learning strategies carried out by PAI teachers included always attending students during PJJ, assessing the results of student assignments, and invoicing students who had not submitted assignments. Meanwhile, learning innovations made by PAI teachers are implementing PJJ using varied and innovative applications such as Google Mail, Google Internet, Google Classroom, Google Forms, Google Drive, Google Meet, Zoom Meet, Youtube, WhatssApp, PDF and Microsoft Power Point.